Pengaruh Corporate Social Responsibility (CSR) Pada Market Value Added (MVA) Perusahaan Manufaktur Dan Pertambangan - Rezi Setin Novian; Santi Novita (Universitas Airlangga, 2013)
Along with the increase of information disclosure needs by stakeholder, the companies are not only demanded to be responsible for merely economic aspect but also environmental and social aspects. The objective of this research to provide the evidence of the effect of Corporate Social Responsibility (CSR) disclosure to the companies performance using Market Value Added (MVA). The research is using manufacturing and mining companies that listed in Bursa Efek Indonesia (BEI) from the year 2007 to 2011 as samples. The hypothesis was tested using t test and the result of this study is Corporate Social Responsibility (CSR) has positive effect on Market Value Added (MVA).